UPAYA MENINGKATKAN NIAT PEMBELIAN PRODUK RAMAH INGKUNGAN MELALUI NILAI, RESIKO, DAN KEPERCAYAAN TERHADAP PRODUK HIJAU - Jati Waskito (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
This study aims to analyze the public perception of value, risk, and trust of green products and developing green marketing model by considering the environmental friendliness of the product, the perception of the value of products, and the risk of products to enhance the consumer's intention to purchase green products. Survey methods to get 292 respondents. Using a structuralequations mode,  found that the public reward and risk products significantly influence consumers' willingness to buy green products. While the trust is not able to increase green purchasing their desires, and cannot be moderating appreciation green value and green risk to increase greenpurchasing green       Key Words: Green Purchasing, value, trust, risk